EFFECTIVE USAGE OF TECHNOLOGICAL MEANS IN UZBEK SCHOOLS (Conferencea, 2022)
this article illustrates some advantages of using technological tools like computers, overhead projector, dynamics, power point presentations in primary schools. Moreover, it gives some ideas how to use correctly these tools.